Penzion na cyklostezce - Jirka, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Předmětem diplomové práce je novostavba penzion na cyklostezce v obci Spálené Poříčí. Objekt je navržen na mírně svažitém terénu směrem na západ. Hlavní vstup je orientován na jih. Jedná se o objekt bez podsklepení s dvěma nadzemními podlažími. Nosnou konstrukcí budovy je příčný stěnový systém z keramických tvarovek. Ostatní zdivo je též z keramických tvarovek. Celý objekt je založen na základových pasech a patkách. Penzion je zastřešen v ubytovací i restaurační části sedlovou střechou. Pro restaurační část je navržena letní terasa na západní straně objektu. V této práci je částečně řešena statika a technické zařízení budovy. Objekt je také zhodnocen z hlediska osvětlení, tepelných požadavků a akusticky. Dále je řešena i požární bezpečnost staveb.

The subject of this thesis is a design of a newly built guesthouse on a bicycle path in the village Spálené Poříčí. The building is designed in a gently sloping terrain towards the west. The main entrance faces the south. It is an object without a basement and with two above ground floors. The structure of the building is a transverse wall system made of ceramic fittings. Other walls are also made of ceramic fittings. The entire building is based upon the stripe foundations and footings. Pension is covered in the part of the accommodation and in the restaurant part with a gable roof. For the restaurant, a terrace is designed on the west side of the building. In this thesis, static and building equipments are solved. The building is also evaluated in the terms of lighting, thermal, acoustic requirements and the fire safety of building is also solved.
Lodging house for cyclists
Keywords: Příčný systém; základový pás; železobetonová stropní deska; železobetonový sloup; keramická tvarovka; sedlová střecha; penzion; požární bezpečnost; tepelné ztráty; tepelný odpor; akustika; Transverse system; strip foundation; concrete slab; reinforced concrete column; ceramic tile; gabled roof; guesthouse; fire safety; heat losses; heat resistance; acoustics